Jewish law from Jesus to the Mishnah five studies - Sanders, Ed Parish, 1937- (London, UK SCM, 1990)
Includes bibiographical references and indexes.
Keywords: Jewish law -- history; Judaism -- history -- Talmudic period, 10-425.; Jesus Christ -- views on Jewish law; Pharisees